Conjugating Prussian blue nanoparticles onto antigen-specific T cells as a combined nanoimmunotherapy. (July 2016) - Burga, Rachel A; Patel, Shabnum; Bollard, Catherine M; Y Cruz, Conrad Russell; Fernandes, Rohan
Aim: To engineer a novel nanoimmunotherapy comprising Prussian blue nanoparticles (PBNPs) conjugated to antigen-specific cytotoxic T lymphocytes (CTL), which leverages PBNPs for their photothermal therapy (PTT) capabilities and Epstein–Barr virus (EBV) antigen-specific CTL for their ability to traffic to and destroy EBV antigen-expressing target cells.Materials & methods: PBNPs and CTL were independently biofunctionalized. Subsequently, PBNPs were conjugated onto CTL using avidin–biotin interactions. The resultant cell-nanoparticle construct (CTL:PBNPs) were analyzed for their physical, phenotypic and functional properties.Results: Both PBNPs and CTL maintained their intrinsic physical, phenotypic and functional properties within the CTL:PBNPs.Conclusion: This study highlights the potential of our CTL:PBNPs nanoimmunotherapy as a novel therapeutic for treating virus-associated malignancies such as EBV+ cancers.